Implementasi Kebijakan Elektronik Voting dalam Pemilihan Kepala Desa di Kabupaten Boyolali Tahun 2013 - Mahardika, Satya; Yuwono, Teguh; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2017)
This research aims to examine about the village heads election at Boyolali District in 2013 that is using a new method, namely electronics election (electronic voting). E-voting methods are used only in 8 villages, namely Kebonbimo Village, Kebongulo, Gondang Slamet, Sambi, Trayu, Genting, Karangnongko, and Dologan Villages. The use of e-voting is conducted to reduce errors and barriers which occur ini elections by conventional means. This research analyzes use of implementation factors expressed by van Meter and van Horn are; 1) Standard and Policy Goals; 2) Resource; 3) Communications; 4) Implementating Agent Characteristics; 5) Disposition; 6) Environmental Conditions (social, economic, polital).Â The methods used in the study is a research method in combination with qualitative and quantitative approach with a descriptive method. In obtaining the data, the researcher use research tools interviews with research informants is the District Secretariat of Boyolali District, Election Committee of the district and of the village and then distributed questuinnaire spread to the community. The research also use secondary data derived form documentation contained in the District Secretariat of Boyolali District and also other literature sources such as books and journals.Results of this research showed that the implementation of e-voting has been implemented by the Government which is also supported by the villager. The villager is satisfied with use of methods of e-voting in an election. Implementation of e-voting in Boyolali District also reached the goals, that is to reduce errors that occur in election, especially in the vote count. In addition to the support resources also have an important role in the execution of a program. Communication is intertwined between the Committee, the Committee of village, district, and also the villager looks satisfied towards using of method of e-voting. social condition, economy, and politics is not so influential in the implementation of e-voting, because the villager felt that use of methods of e-voting in election already as applied in Indonesia not to outmoded.